STRATEGI PENGEMBANGAN KAWASAN AGROWISATA BERBASIS MASYARAKAT DI KOTA SOLOK, SUMATERA BARAT - Puspitasari Puspitasari; Adhitya Marendra Kiloes (Jurnal Pengkajian dan Pengembangan Teknologi Pertanian, 2021)
Strategy for Agricultural Technology Innovation-Based Agro-tourism Development in Solok City, West Sumatera. Agro-tourism area is an agricultural-based tourism area aimed at increasing the community income. One of the potential agro-tourism areas to be developed is the Payo agro-tourism area in Solok City, West Sumatra. The development of the Payo Agro-tourism Area aims to create a sustainable agro-tourism area and improve the economy and welfare of the community and farmers. Therefore, it is necessary to identify the factors of strengths and opportunities that can support and weaknesses and threats that can become obstacles in developing the agro-tourism area, then formulate an appropriate strategy for its development. This study aims to analyze the community-based agro-tourism development strategy in Solok City. The research was conducted in 2018, with the determination of research respondents carried out by purposive sampling, which is based on the criteria of respondents who are stakeholders or actors who have an interest in developing the Payo agro-tourism area in Solok. Data and information were analyzed using SWOT and QSPM to determine strategic priorities. The SWOT analysis results show 10 alternative strategies such as the development of superior fresh and processed products as agro-tourism icons, technical guidance on cultivation and post-harvest technology, promotion through social media, plant rejuvenation and technology application, the establishment of community institutions, arrange the production planning, arrange agro-tourism management planning, government budgeting support, build supporting facilities and infrastructure, managerial training for agro-tourism management. Based on the results of the QSPM analysis, the most appropriate strategy to prioritize is budgeting support from local governments in terms of promotion and improvement of the quality of tourism objects. Keywords: agro-tourism, strategy, SWOT, QSPM ABSTRAK Kawasan agrowisata merupakan kawasan wisata berbasis pertanian yang ditujukan untuk meningkatkan pendapatan masyarakat di dalam kawasan. Salah satu kawasan agrowisata yang potensial untuk dikembangkan adalah kawasan agrowisata Payo di Kota Solok, Sumatera Barat. Pengembangan Kawasan Agrowisata Payo ini bertujuan untuk menciptakan kawasan agrowisata yang berkelanjutan, serta meningkatkan perekonomian dan kesejahteraan masyarakat dan petani. Oleh karena itu perlu diidentifikasi faktor-faktor kekuatan dan peluang yang dapat mendukung, serta kelemahan dan ancaman yang dapat menjadi hambatan dalam pengembangan kawasan agrowisata tersebut, kemudian dirumuskan suatu strategi yang tepat untuk pengembangannya.  Penelitian ini bertujuan untuk   menganalisis strategi pengembangan kawasan agrowisata berbasis masyarakat di Kota Solok. Penelitian dilakukan pada tahun 2018, dengan penentuan responden penelitian dilakukan secara purposive sampling yaitu berdasarkan kriteria responden yang merupakan stakeholders yang berkepentingan terhadap pengembangan kawasan agrowisata Payo di Kota Solok. Data dan informasi dianalisis menggunakan SWOT dan  QSPM untuk mengetahui prioritas strategi. Dari hasil perumusan analisis SWOT diperoleh 10 alternatif strategi yaitu pengembangan produk segar dan olahan unggulan sebagai ikon agrowisata, bimbingan teknis mengenai teknologi budidaya dan pasca panen, promosi melalui media sosial, peremajaan tanaman dan penerapan teknologi, pembentukan kelembagaan masyarakat, penyusunan rencana produksi, pembuatan rencana manajemen pengelolaan agrowisata, dukungan  penganggaran dari pemerintah, melengkapi sarana dan prasarana, serta pelatihan manajerial bagi SDM pengelola agrowisata. Berdasarkan hasil analisis QSPM strategi yang paling tepat untuk diprioritaskan adalah dukungan penganggaran dari pemerintah daerah dalam hal promosi dan peningkatan kualitas obyek wisata. Kata kunci: agrowisata, strategi, SWOT, QSPM,